Opioid combination. Case report - Brzeziński, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2011)
The combination of long-acting opioids has not been sufficiently documented in the literature. Patient J.L., aged 67, with disseminated malignant process. Complaints of pelvic and visceral pain. Treatment: sustained release morphine 60 mg/daily. There occurred a need to increase the dose of the drug up to 120 mg/daily; the patient was referred to the Pain Management Outpatient Department. Nociceptive pain was diagnosed at the intensity of 7.5 on the VAS scale. Ketoprofen was included in the treatment at a dose of 200 mg/daily. After three days the morphine dose was increased to 180 mg/daily. Due to the lack of adequate pain control sustained release oxycodone was started, initially at a dose of 20 mg/ daily, and after three days 40 mg/daily. After two weeks, the dose of morphine was decreased to 140 mg/daily. Adequate pain control was obtained.